Co-selection phenomena across New Englishes: parallels (and differences) to foreign learner varieties - Nesselhauf, Nadja (English world-wide, 2009)
Similarities of the phraseology of institutionalized second language varieties and foreign learner varieties have gone almost completely unnoticed so far. In this paper, different types of co-selection phenomena are examined across ESL and EFL varieties on the basis of the ICE-corpora of Kenyan, Indian, Singaporean, and Jamaican English and of ICLE, the International Corpus of Learner English. Among the features investigated are the use of competing collocations such as play a role and play a part, the noun complementation of collocations (HAVE + INTENTION + of -ing vs. to + infinitive), and non-L1 (or “new”) prepositional verbs such as comprise of, demand for or emphasize on. The exploration shows that many co-selection phenomena do indeed recur not only across individual institutionalized L2 varieties but also across the two variety types. Certain kinds of language-internal irregularities in the phraseology of Standard English are shown to be a major reason for the observed parallels